The Compensatory Role of Diverse Workplaces: Parental Workplace Educational Composition and Children's Higher Education Enrolment - Heiskala, Laura; Pruel, Margus (Wiley, 2026)
Studies consistently find family background differences in educational attainment, with parental education being an important factor in families' educational decision-making processes. Alongside parents’ own resources and accomplishments, research has shown that both immaterial and material resources from extrafamilial connections, such as extended family members, are positively associated with children's educational attainment and may compensate for a lack of resources within the immediate family. In this study, we examine the compensatory role of parental workplace ties in shaping children's educational choices. Using full population register data from Finland, we find that children from lower-educated families are more likely to enrol in higher education if they have a parent working among highly educated colleagues. We discuss the importance of diverse environments for educational mobility and aim to shed new light on the role of weak ties in educational decision-making.